Wang Yangming’s Concept of Oneness from the Perspective of Mysticism - Liu, Linna (Religions, 2024)
Wang Yangming’s emphasis on the concept of oneness establishes a significant connection between his philosophy and mysticism. This comparative study draws upon his mystical encounters and conceptual framework. Although “all things form one body” appears to be a typical formula of extrovertive mysticism, his doctrine is more inclined to be classified as a type of introvertive mysticism because of the special definition of “thing” and the deep involvement of heart–mind. The realm of oneness is based on the mode of a heart–mind pervading the entirety of the universe and all things, with the core concept of liangzhi as both pure consciousness and the base of the world. The adoption of a mystical philosophical perspective highlights Wang’s theory of oneness as a spiritual philosophy, transcending general ethical claims, thus enriching our understanding of Wang’s philosophy of mind.